Excessive Sensitivity to Uncertain Visual Input in L-DOPA-Induced Dyskinesias in Parkinson’s Disease: Further Implications for Cerebellar Involvement - Stevenson, James; Lee, Chonho; Lee, Bu Sung; Talebifard, Pouria; Ty, Edna B.; Aseeva, Kristina; Oishi, Meeko; McKeown, Martin (Frontiers in Neurology, 2014)
When faced with visual uncertainty during motor performance, humans rely more on predictive forward models and proprioception and attribute lesser importance to the ambiguous visual feedback. Though disrupted predictive control is typical of patients with cerebellar disease, sensorimotor deficits associated with the involuntary and often unconscious nature of L-dopa-induced dyskinesias in Parkinson’s disease (PD) suggests dyskinetic subjects may also demonstrate impaired predictive motor control. Methods: We investigated the motor performance of 9 dyskinetic and 10 non-dyskinetic PD subjects on and off L-dopa, and of 10 age-matched control subjects, during a large-amplitude, overlearned, visually-guided tracking task. Ambiguous visual feedback was introduced by adding ‘jitter’ to a moving target that followed a Lissajous pattern. Root mean square (RMS) tracking error was calculated, and ANOVA, robust multivariate linear regression and linear dynamical system analyses were used to determine the contribution of speed and ambiguity to tracking performance. Results: Increasing target ambiguity and speed contributed significantly more to the RMS error of dyskinetic subjects off medication. L-dopa improved the RMS tracking performance of both PD groups. At higher speeds, controls and PDs without dyskinesia were able to effectively de-weight ambiguous visual information. Conclusions: PDs’ visually-guided motor performance degrades with visual jitter and speed of movement to a greater degree compared to age-matched controls. However, there are fundamental differences in PDs with and without dyskinesia: subjects without dyskinesia are generally slow, and less responsive to dynamic changes in motor task requirements but, PDs with dyskinesia there was a trade-off between overall performance and inappropriate reliance on ambiguous visual feedback. This is likely associated with functional changes in posterior parietal-ponto-cerebellar pathways.